2016
DOI: 10.1007/s10339-016-0755-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of filled pauses on the processing of the surface form and the establishment of causal connections during the comprehension of spoken expository discourse

Abstract: The purpose of this study was to examine the effect of filled pauses (uh) on the verification of words and the establishment of causal connections during the comprehension of spoken expository discourse. With this aim, we asked Spanish-speaking students to listen to excerpts of interviews with writers, and to perform a word-verification task and a question-answering task on causal connectivity. There were two versions of the excerpts: filled pause present and filled pause absent. Results indicated that filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
2
0
2
Order By: Relevance
“…Results indicated that the presence of the discourse marker facilitated the reactivation of prior causally connected statements. Cevasco and van den Broek (2016) observed that the presence of filled pauses (such as 'uh') had a negative effect on the recognition of spoken words, but not on the generation of causal inferences. These results suggest that the generation of these inferences plays a role in the processing of spoken discourse by college students.…”
Section: Empirical Findings and Applications Of The Model To Education And Learningmentioning
confidence: 98%
“…Results indicated that the presence of the discourse marker facilitated the reactivation of prior causally connected statements. Cevasco and van den Broek (2016) observed that the presence of filled pauses (such as 'uh') had a negative effect on the recognition of spoken words, but not on the generation of causal inferences. These results suggest that the generation of these inferences plays a role in the processing of spoken discourse by college students.…”
Section: Empirical Findings and Applications Of The Model To Education And Learningmentioning
confidence: 98%
“…A su vez, los materiales presentados por las investigaciones realizadas no han tendido a involucrar discurso espontáneo. Esta brecha es importante, dado que como se mencionó, los materiales no espontáneos podrían no reflejar los procesos involucrados en la comprensión del discurso durante la participación social en el ámbito cotidiano (Cevasco y van den Broek, 2016;Cossavella y Cevasco, 2021;Fraundorf y Watson, 2011). En relación con esto, estudios preliminares sugieren que la generación de inferencias causales facilita la comprensión del discurso oral espontáneo, dado que promueve el recuerdo de enunciados, la respuesta a preguntas de comprensión (Cevasco, 2009;Cevasco y van den Broek, 2008), la identificación de cambios de tema (Cevasco et al, 2020) y el recuerdo de enunciados emocionales (de Simone y .…”
Section: Preguntas De Elaboración Y Comprensión Del Discurso Expositivounclassified
“…En relación con esto, estudios preliminares sugieren que la presencia de marcadores del discurso ('pero') facilita la generación de inferencias de restablecimiento (Cevasco, 2009). A su vez, indican que la presencia de pausas marcadas por 'eh' perjudica el reconocimiento de palabras previamente escuchadas, pero no la generación de estas inferencias (Cevasco & van den Broek, 2016). Estos estudios contribuyen a comenzar a investigar el rol del interjuego entre la generación de inferencias causales y las características del discurso oral espontáneo, y destacan la importancia de realizar nuevos estudios acerca de este tema.…”
Section: Brechas En La Investigación Acerca Del Modelo Y Futuras Dire...unclassified